Comparison of Deep Learning Architectures in Identifying Types of Medicinal Plant Leaf Images - Salsabila, Sarah; Suharso, Aries; Purwantoro, Purwantoro (Politeknik Negeri Batam, 2024)
This study focuses on the identification of 3500 images of medicinal plant leaves using Deep Learning CNN Transfer Learning models such as MobileNet, VGG16, DenseNet121, ResNet50V2, and NASNetMobile. The dataset used is the